A Roadmap for Understanding the Evolutionary Significance of Structural Genomic Variation. (July 2020) - Mérot, Claire; Oomen, Rebekah A.; Tigano, Anna; Wellenreuther, Maren
Abstract : Structural genomic variants (SVs) are ubiquitous and play a major role in adaptation and speciation. Yet, comparative and population genomics have focused predominantly on gene duplications and large-effect inversions. The lack of a common framework for studying all SVs is hampering progress towards a more systematic assessment of their evolutionary significance. Here we (i) review how different types of SVs affect ecological and evolutionary processes; (ii) suggest unifying definitions and recommendations for future studies; and (iii) provide a roadmap for the integration of SVs in ecoevolutionary studies. In doing so, we lay the foundation for population genomics, theoretical, and experimental approaches to understand how the full spectrum of SVs impacts ecological and evolutionary processes. Highlights: Structural genomic variants (SVs) take diverse forms and are ubiquitous drivers of ecological and evolutionary processes. Most studies of SVs focus on the adaptive significance of gene duplications and large inversions. Future studies should catalog SVs of all types and sizes and systematically test their evolutionary implications. We propose a roadmap and definitions for the study of SVs in ecological and evolutionary genomics. Best practices for SV detection are needed to facilitate comparisons across studies. Integrating population genomic, theoretical, and experimental approaches to SVs will more comprehensively characterize genomic variation, uncover the adaptive and neutral processes shaping the evolutionary trajectory of SVs, and identify the mechanisms by which SVs impact adaptation and speciation.